Предмет: Алгебра,
автор: Rita2121
(а-¹ + 3)² - ( а-¹ — 2)² - 10:а
Ответы
Автор ответа:
0
(а^-1+3–а^-1+2)(а^-1+3+а^-1–2)–10/а =
= 5(а^-2+1)–10/а = 5/а^2+5–10/а =
= (5+5а^2–10а)/а^2=5(1+а^2–2а)/а^2
= 5(а–1)^2/а^2
= 5(а^-2+1)–10/а = 5/а^2+5–10/а =
= (5+5а^2–10а)/а^2=5(1+а^2–2а)/а^2
= 5(а–1)^2/а^2
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Другие предметы,
автор: arinakuznecova0672
Предмет: Английский язык,
автор: kayrat2122
Предмет: Информатика,
автор: mashagoglova777777
Предмет: Геометрия,
автор: Zahar123321
Предмет: Математика,
автор: nyashanatasha234